2000
DOI: 10.1080/028418500127345442
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive myocardial iron assessment in thalassaemic patients: T2 relaxometry and magnetization transfer ratio measurements

Abstract: MTR measurements can be used to complement T2 measurements for non-invasive myocardial iron assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Iron has been shown to affect the magnetization transfer effect in the brain (Smith et al, 2009), and has been exploited in MTR imaging of rectal cancer to detect fibrosis (Martens et al, 2014;Papanikolaou et al, 2000). It has been suggested that iron is an important indicator of different physiological and pathological processes in MS (Bagnato et al, 2013), and we therefore investigated whether iron could have influenced out MTR changes.…”
Section: Discussionmentioning
confidence: 99%
“…Iron has been shown to affect the magnetization transfer effect in the brain (Smith et al, 2009), and has been exploited in MTR imaging of rectal cancer to detect fibrosis (Martens et al, 2014;Papanikolaou et al, 2000). It has been suggested that iron is an important indicator of different physiological and pathological processes in MS (Bagnato et al, 2013), and we therefore investigated whether iron could have influenced out MTR changes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in acute MI, myocardial capillary damage leads to hemorrhage which may be enhanced by coronary reperfusion (1-3). However, in vivo MRI studies have been limited due to artifacts from cardiorespiratory motion and blood flow (5). While advances in MRI now enable detection of hemorrhage in the human heart (6), current dark blood T 2 -weighted MRI techniques are limited by surface coil intensity problems and spin echo artifact (7), which may reduce diagnostic accuracy clinically (7, 8).…”
mentioning
confidence: 99%
“…3), a finding previously reported (6), reflecting the different factors involved in tissue iron distribution. In contrast to the findings presented by Galia et al (1), as well as by other investigators (7), no statistical correlation was found between ferritin and heart MRI.…”
mentioning
confidence: 62%